Enhanced GeSn Microdisk Lasers Directly Released on Si. Issue 2 (21st November 2021) - Kim, Youngmin; Assali, Simone; Burt, Daniel; Jung, Yongduck; Joo, Hyo‐Jun; Chen, Melvina; Ikonic, Zoran; Moutanabbir, Oussama; Nam, Donguk
Abstract: GeSn alloys are promising candidates for complementary metal‐oxide‐semiconductor‐compatible, tunable lasers. Relaxation of residual compressive strain in epitaxial GeSn has recently shown promise in improving the lasing performance. However, the suspended device configuration that is thus far introduced to relax the strain is destined to limit heat dissipation, thus hindering the device performance. Herein is demonstrated that strain‐free GeSn microdisk laser devices fully released on Si outperform the canonical suspended devices. This approach allows to simultaneously relax the limiting compressive strain while offering excellent thermal conduction. Optical simulations confirm that, despite a relatively small refractive index contrast between GeSn and Si, optical confinement in strain‐free GeSn optical cavities on Si is superior to that in conventional strain‐free GeSn cavities suspended in the air. Moreover, thermal simulations indicate a negligible temperature increase in the device. Conversely, the temperature in the suspended devices increases substantially reaching, for instance, 120 K at a base temperature of 75 K under the employed optical pumping conditions. Such improvements enable increasing the operation temperature by ≈40 K and reducing the lasing threshold by 30%. This approach lays the groundwork to implement new designs in the quest for room temperature GeSn lasers on Si. Abstract : Germanium‐tin (GeSn) alloys are promising candidates for on‐chip lasers. Herein, it is demonstrated that GeSn microdisk lasers released on silicon (Si) outperform the suspended lasers. Improvements in optical and thermal properties enable higher operation temperature of up to 110 K in the lasers on Si and also allow observing reduced lasing thresholds of <60 kW cm −2 at 4 K.